RACIAL PREJUDICE IN WILL EISNER’S FAGIN THE JEW GRAPHIC NOVEL - N, Asyipa; Kusumoriny, Laksmy Ady (EUFONI: Journal of Language, Literary, and Cultural Studies, 2022)
This study discusses racial prejudice issue experienced by main character in a graphic novel entitled Fagin The Jew by Will Eisner (2003). This study aims to explore the racial prejudice through the prejudice scale as the manifestation of prejudice action and also reveal the ego defense as the response to prejudice. The method used in conducting this study is qualitative approach and the theory of prejudice by Allport (1954) is used to analyze the data. The results show that there are four scales of prejudice act occur within the story. These scales are verbal rejection (antilocution), avoidance, discrimination, and physical attack. Moreover, the study exposes that the victims did some ego defenses mechanism, namely denial of membership, slyness and cunning and enhanced striving.